2010
DOI: 10.1111/j.1600-079x.2010.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐nucleotide polymorphisms and mRNA expression for melatonin synthesis rate‐limiting enzyme in recurrent depressive disorder

Abstract: Depressive disorder (DD) is characterised by disturbances in blood melatonin concentration. It is well known that melatonin is involved in the control of circadian rhythms, sleep included. The use of melatonin and its analogues has been found to be effective in depression therapy. Melatonin synthesis is a multistage process, where the last stage is catalysed by acetylserotonin methyltransferase (ASMT), the reported rate-limiting melatonin synthesis enzyme. Taking into account the significance of genetic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 63 publications
2
40
0
4
Order By: Relevance
“…In depressed patients, DLMO is usually delayed and melatonin levels are decreased (67,68). In depressive patients there are some single nucleotide polymorphisms (SNPs) in the melatonin pathway such as arylalkylamine N-acetyltransferase (AANAT) (69) and a rate-limiting melatonin enzyme acetylserotonin methyltransferase (ASMT) (70). Melatonin is a prototype of chronobiotics and the chemical code of darkness (43).…”
Section: Melatonin and Melatonin Agonistsmentioning
confidence: 99%
“…In depressed patients, DLMO is usually delayed and melatonin levels are decreased (67,68). In depressive patients there are some single nucleotide polymorphisms (SNPs) in the melatonin pathway such as arylalkylamine N-acetyltransferase (AANAT) (69) and a rate-limiting melatonin enzyme acetylserotonin methyltransferase (ASMT) (70). Melatonin is a prototype of chronobiotics and the chemical code of darkness (43).…”
Section: Melatonin and Melatonin Agonistsmentioning
confidence: 99%
“…Brain inflammatory processes are causally related to the enhanced neurodegeneration changes and reduced neurogenesis observed in the course of depression. Moreover, numerous studies have found that depression is associated with elevated levels of proinflammatory cytokines (Kubera et al 2000;Maes et al 2009;Dowlati et al 2010;Szczesny et al 2014) and with an increased rate of single nucleotide polymorphisms within proinflammatory genes (Galecki et al 2010). Microglia are considered the main source of cytokines in the brain (Hanisch 2002).…”
mentioning
confidence: 99%
“…Allelic variants SNP rs17070145 are considered as genetic link between features of the memory mechanisms and anxiety and depressive disorders. Results of researches indicates that variants of more efficiency of hippocampal LTP and higher performance of episodic memory ("CT" and "TT") are associated with increasing the likelihood of PTSD development [33], while "CC" variant rs17070145 is associated with depressive disorder [34]. Role of the immune system in synaptic plasticity is becoming increasingly apparent [35][36][37].…”
Section: Introductionmentioning
confidence: 99%